ANCA-associated vasculitis presenting with progressive binocular manifestations: a case report and literature review - Xi, Lei; Cui, Ying; Li, Zhilian (Frontiers in Medicine, 2024)
This report primarily describes a rare case of an elderly male patient who initially presented with central retinal artery occlusion (CRAO) in the left eye and was ultimately diagnosed with anti-neutrophil cytoplasmic antibody (ANCA) -associated vasculitis involving the eyes, gastrointestinal tract, and kidneys. However, due to irregular treatment, both eyes developed progressive ocular manifestations later. This article emphasizes the importance of actively screening for and treating underlying conditions in cases of CRAO. A comprehensive assessment of the patient’s medical history, systemic condition, and ocular examination can aid in early diagnosis, slow disease progression, and reduce mortality.